Sistema de monitoramento guiado remotamente - Meurer, Rafael de Farias (2014)
Due to the increasing sense of insecurity, many people are choosing to hire private security services. Among these, the most wanted is the surveillance cameras, this technology has been changed in many ways until it gets at the current state, which can be accessed via IP cameras. The next step is to get the cameras the freedom of movement and rotation in order to increase the coverage area of monitoring. With this point in mind, this project aims to design a monitoring system remotely guided. For its construction, a robot was esigned, where the camera is attached, and a graphical user interface, programmed in Java, so the user can connect and control the robot, and watch the environment. This project makes use of a network interface 802.11 wireless for greater mobility robot, a Linux embedded operating system, which allows you to use all the peripherals drivers, in addition to having TCP/IP stack implemented, which is essential in this project due to the need of using UDP and TCP transporting protocols. The control software of the system, which runs on a Embedded Linux operating system, was coded in Python, this software receives commands from the graphical interface and executes them. The camera used is a web-cam, which has got satisfactory resolution for monitoring, this camera has degrees of freedom even with the robot stopped. The video of the environment can be compressed using the MPEG-4 Part 2 algorithm, by using the GStreamer library, if the user wants to reduce the bandwidth consumption. At the end of the project, tests to check the system requirement were done, which were successful, therefore the goal of this project was successfully achieved.